Entrepreneurship education: Exploring the missing piece in Ethiopian primary and secondary education pogrammes - Adane Tessera Biru; Reda Darge Negassi (Bahir Dar Journal of Education)
For decades unemployment in developing countries particularly in sub-Saharan Africa has been mounting. Recent world financial crisis has also resulted in unemployment at vast levels. To employ these unemployed persons is a big challenge for authorities. In hard times when educated persons can’t get jobs, it becomes a challenge for states. It is rather harder for developing countries, like Ethiopia, where governments do not have sufficient resources to support the unemployed workforce. Self-employment and entrepreneurship is referred not only as the best solution but also strategically recognized as a competitive advantage for national development and a global future. Entrepreneurship, job creation and enterprise development are currently at the front in the Ethiopian policy agenda. Job creation and enterprise development skills have become more crucial concerns of policy makers, the public and individual citizens more than ever. Graduates from different educational institutions at different levels should not be job seekers in no way. Government policies and programs confirm that graduates should be the movers and shakers of the enterprise. However, this review is critical of the efficacy of Ethiopian government’s agenda of entrepreneurship, arguing that students should not wait for TVET or university education to develop attitudes toward entrepreneurship as a career alternative. The review challenges why primary and secondary school students are waiting for graduation for developing entrepreneurial intent as a policy concern and a career development agenda among young citizens